2003
DOI: 10.4028/www.scientific.net/msf.433-436.443
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hall Mobility in 4H-SiC for Improvement of the Accuracy of the Mobility Model in Device Simulation

Abstract: In order to construct a reliable parameter set for the physical modeling of 4H-SiC, we are collecting and examining the physical parameters. The results of mobility measurement are presented and compared with the built-in model in the device simulator. The doping dependence of the electron mobility is in agreement with the built-in model, whereas that of the hole mobility is different from the built-in model in the higher doping region. Further, the anisotropy of the electron and hole mobility is investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…Recently the dependence of hole mobility on the freehole concentration in p-type 4H-SiC has been estimated using the following semi-empirical equation 25 by Hatakeyama et al 26 The estimated curve is shown by the dashed curve in Fig. 7…”
Section: Discussion Of the Electrical Properties In P + -Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the dependence of hole mobility on the freehole concentration in p-type 4H-SiC has been estimated using the following semi-empirical equation 25 by Hatakeyama et al 26 The estimated curve is shown by the dashed curve in Fig. 7…”
Section: Discussion Of the Electrical Properties In P + -Sicmentioning
confidence: 99%
“…Using the parameters as given in Ref. In their report, 26 the parameters in the Eq. 7(b) is obtained.…”
Section: ͑2͒mentioning
confidence: 99%
“…The details of the growth conditions were reported in the previous paper. 36 One 10 m thick p-type 4H-SiC epilayer on an n + -type 4H-SiC(0001) substrate (sample number: No. 6) was purchased from Cree Res.…”
Section: Methodsmentioning
confidence: 99%
“…Three 10-m-thick n-type 4H-SiC epilayers with different N-doping densities were grown on p + -type 4H-SiC substrates, 15 and another three 10-m-thick n-type 4H-SiC epilayers grown on p + -type 4H-SiC substrates were pur-chased from Cree Inc. They were cut into a 3 ϫ 3-mm 2 size.…”
Section: Methodsmentioning
confidence: 99%